The presence and persistence of entrepreneurship education In Indonesia: a cross sectional study - Ambara Purusottama; Teddy Trilaksono (International Journal of Evaluation and Research in Education (IJERE), 2019)
This study aims to improve an understanding of the contribution of entrepreneurship education (EE) in Indonesia’s higher education. Even though the contribution of EE to global education is contested at the present time by many scholars, the evaluation of EE implementation in Indonesia is necessary in order to improve educated entrepreneurs. The study used a cross-sectional approach in the Universitas Prasetiya Mulya which is divided into the first, second, and third years. Valid questionnaire reached 924 respondents. The findings show that EE's contribution in Indonesia has more influence on attitudes and perceived behavioral control. However, other findings indicate that the contribution of EE is still not fully persistent due to a sharp decline in the regression coefficient, especially from subjective norm and perceived behavioral control in the students third year while attitude consistently contributes significant role and has an increasing contribution.